2019
DOI: 10.1038/s41598-019-50162-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of β-CD-DPPE-Dox Nanomedicine and Its’ Application as the Anticancer and Antitumor Drug

Abstract: β-CD-DPPE molecule was synthesized through the conjugation of β-CD-NH2 and the DPPE molecule, and its’ water-solubility was more excellent than the traditional phospholipid molecule. The spherical micelles was formed by β-CD-DPPE molecule in aqueous solution, and the β-CD-DPPE-Dox nanomedicine can be prepared through loading Dox (Doxorubicin) into the micelles, and the Dox loading ratio was about 82.3 ± 7.27%. At the same time the Dox release behavior from the nanomedicine was sustained-release and pH controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Seen from Figure 4a, the relative viability of HepG2 cells and HepG2 cells was about 90% for 24 h incubation when the biotin-HSA-DDA-TCPP aggregates reached 30 μg•mL −1 , and the relative cell viability was 81.4% for 48 h incubation, which indicated that the biotin-HSA-DDA-TCPP aggregates have low toxicity, and the reason may be due to the excellent biocompatibility of aggregates, which are endowed by HSA; nontoxicity of aggregates is a prerequisite for the use as a drug carrier. 30 Figure 4a,c shows that the biotin-HSA-DDA-TCPP-Dox nanoparticles (30 μg• mL −1 ) were incubated with HepG2 cells and H22 cells for 24 h, and the cell relative viabilities were 70 and 65%, respectively. Figure 4b,d shows that the relative cell viabilities were 39 and indicated that the nanoparticles had a stronger effect on HepG2 cells than on H22 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Seen from Figure 4a, the relative viability of HepG2 cells and HepG2 cells was about 90% for 24 h incubation when the biotin-HSA-DDA-TCPP aggregates reached 30 μg•mL −1 , and the relative cell viability was 81.4% for 48 h incubation, which indicated that the biotin-HSA-DDA-TCPP aggregates have low toxicity, and the reason may be due to the excellent biocompatibility of aggregates, which are endowed by HSA; nontoxicity of aggregates is a prerequisite for the use as a drug carrier. 30 Figure 4a,c shows that the biotin-HSA-DDA-TCPP-Dox nanoparticles (30 μg• mL −1 ) were incubated with HepG2 cells and H22 cells for 24 h, and the cell relative viabilities were 70 and 65%, respectively. Figure 4b,d shows that the relative cell viabilities were 39 and indicated that the nanoparticles had a stronger effect on HepG2 cells than on H22 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of Dox released was measured at 37 °C. Buffer solution (4 mL) was taken out from the buffer solution outside the dialysis bag for UV-visible spectrophotometer detection (detection wavelength is 485 nm) at different times (1,2,4,8,12,24,36,48,72,84,96,108, and 120 h), whereas 4 mL fresh buffer solution was added into the buffer solution outside the dialysis bag.…”
Section: The Release Behavior Of Dox From the La-peg-g-dox Nanomedicinementioning
confidence: 99%
“…The Zeta potential of the LA-PEG-G aggregates was −35.80 mV in the aqueous solution, which indicated that the surface of the LA-PEG-G aggregates was negatively charged in aqueous solution. A high Zeta potential allows the LA-PEG-G aggregates to maintain good dispersion in aqueous solution [24,25] . The PEG in the LA-PEG-G molecules can help the LA-PEG-G aggregates escape from the trap of Kupffer cells and macrophages in the spleen through scavenger receptors without activating MPS, which help the blood circulation of the LA-PEG-G aggregates in the body [25] .…”
Section: Synthesis Characterization and Aggregationmentioning
confidence: 99%